2021
DOI: 10.1051/metal/2021004
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of supersonic jet behavior in the vacuum refining process

Abstract: There are two problems to be solved in the numerical simulation of the top blown oxygen vacuum refining process. (1) The two-equation turbulence models underpredict the turbulence mixing shear process for high-temperature gradient jet flows. (2) The high compressibility of the jet in a low vacuum environment. In this study, the SST k-ω turbulence model is modified by the composite function of the compressibility factor and the total temperature gradient. Based on the experimental model of the Kotani vacuum jet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…The one is that the empirical Equation ( 11) was obtained under the condition of a singlenozzle jet vertically impinging on liquid surface, without considering the coalescence effect of the multinozzle jet, and another one is that the simulations were conducted at the converter temperature of 1873 K; however, the empirical formula was obtained at room temperature. Many researchers [38][39][40] have observed that the ambient temperature has a significant effect on the dynamic characteristics of the jets, which further affects the cavity shape. In addition, within the allowable range of error, the depth of the cavity obtained by empirical Equation ( 11) is in good agreement with the changing trend of the CFD results.…”
Section: Effect Of Operating Parameters On the Impact Cavitymentioning
confidence: 99%
“…The one is that the empirical Equation ( 11) was obtained under the condition of a singlenozzle jet vertically impinging on liquid surface, without considering the coalescence effect of the multinozzle jet, and another one is that the simulations were conducted at the converter temperature of 1873 K; however, the empirical formula was obtained at room temperature. Many researchers [38][39][40] have observed that the ambient temperature has a significant effect on the dynamic characteristics of the jets, which further affects the cavity shape. In addition, within the allowable range of error, the depth of the cavity obtained by empirical Equation ( 11) is in good agreement with the changing trend of the CFD results.…”
Section: Effect Of Operating Parameters On the Impact Cavitymentioning
confidence: 99%